2022
DOI: 10.3389/fbioe.2022.851094
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Assessment of Heterogeneous Tissue Natural Frequency Using Micro-Force Optical Coherence Elastography

Abstract: Analysis of corneal tissue natural frequency was recently proposed as a biomarker for corneal biomechanics and has been performed using high-resolution optical coherence tomography (OCT)-based elastography (OCE). However, it remains unknown whether natural frequency analysis can resolve local variations in tissue structure. We measured heterogeneous samples to evaluate the correspondence between natural frequency distributions and regional structural variations. Sub-micrometer sample oscillations were induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In contrast, the dynamic OCE, including step, harmonic (sinusoid signal), spectroscopic (chirp signal), or impulse loading methods, characterize the sample response with faster motion features (such as resonation and wave propagation), and these induced motions are strain-rate- and frequency-dependent. Thus, it is essential to characterize the excitation method in the temporal and frequency domains to accurately analyze motion characteristics, such as the potential evoked frequency range [49] , [50] , [244] , [245] and the phase velocity, which is frequency dependent in a viscoelastic sample such as the cornea.…”
Section: In Vivo Ocementioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the dynamic OCE, including step, harmonic (sinusoid signal), spectroscopic (chirp signal), or impulse loading methods, characterize the sample response with faster motion features (such as resonation and wave propagation), and these induced motions are strain-rate- and frequency-dependent. Thus, it is essential to characterize the excitation method in the temporal and frequency domains to accurately analyze motion characteristics, such as the potential evoked frequency range [49] , [50] , [244] , [245] and the phase velocity, which is frequency dependent in a viscoelastic sample such as the cornea.…”
Section: In Vivo Ocementioning
confidence: 99%
“…Natural frequency is an intrinsic property of a sample, which is defined as the frequency at which the sample tends to oscillate when disturbed [280] . Natural frequency oscillation in response to excitation force is intimately connected to tissue elastic properties [49] , [244] , [245] . It has been demonstrated that the natural frequency is linearly related to the square root of Young’s modulus in a simple elastic model.…”
Section: In Vivo Ocementioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of this OCE system has been provided in our previous work [38,39]. In summary, this OCE system was built by combining a microliter air-pulse mechanical stimulation system and a 1290-nm linear-wavenumber (k) spectral domain OCT platform [40] (Figure 1a).…”
Section: Oce System Set-upmentioning
confidence: 99%